Gestalt theory on principles of musical construction and analysis - Surwd Fouad Mohammed; Nasser Hashim Badan; Dlawer Mustafa Mohammed (Zanco Journal of Humanity Sciences)
This research uses Qualitative method in the perspective of music's theory of Gestalt. It also includes borders, research forms, and building in modern music. The Musical forms have come from continuous attempts to experience and apply different musical teas. This has become an artistic method that the composer obtained the ideas of melodies, contrasts and harmonies in the music context. These forms   absolutely, have special principles and methods that determine the composers' duty to these forms and musical structures and then abide by musical performance. The process of building in any literal and artistic form in general expresses civilized and artistic experiences   of the   ongoing experiences of artistic and general intellectual performance of the process. Musical construction is not different from any other art, but rather in the harmony and balance between the subjects that the artist uses. That's why these melodies are exactly the same as musical theories. This gives the composer some kind of freedom. To be absolutely touched in frozen behests and to perform music decisively.